REGIONAL ANALYSES OF THE EDUCATION SYSTEM IN ROMANIA - Adriana Grigorescu (European Regional Science Association (ERSA), 2011)
Education represents one of the fundamentals of the social and economic environment in each and every society, even more in the current stage of development that involves higher educational levels for proper access to technologies. Depending on the specific level of education and training, people are able to find a suitable position in the society by integrating themselves into the labor market. The human potential within a region might be an essential element for embarking the area upon a positive trend in economic development. Without a doubt, the economic environment is primarily attracted to areas rich in human and material resources. Skilled human resources provide an edge especially as the share of the tertiary sector in the economy is becoming larger. Previous research were focused on determining the skill, knowledge and activities management and marketing specialists from the public and private - similarities and differences, selection schemes. A regional analysis of the educational system by taking into account the distribution of infrastructure and the educational categories within the structure of the active population could lead towards an "attractiveness chart" from this perspective. This paper aims to perform specific analyses for various types of infrastructure elements of the individual and integrated educational system in order to emphasize the educational capacity of each county. At the same time, on the basis of data on existing occupational groups in each county and by using the same method, counties can be ranked with respect to the materialized potential of the educational system. The outcomes of the study can be integrated into complex structural analyses, which underpin the public policies on education and employment of workforce and represent a possible approach of the infrastructure and outputs of a system. Organizational change and strategies for medium and long term are out coming of high technologies used by a skilled workforce. Romania is known less as a high-tech generation laboratory, but especially as the skilled workforce and highly qualified with outstanding creative and innovative skills reservoir. That is why the management of technological change should be understood in relationship with the workforce.
Keywords: 330